OVERLAPS USED IN TV PROGRAM “INI TALKSHOW NET TV” - Melinda Manurung; Meisuri Meisuri; Rafika Dewi Nasution (State University of Medan, 2017)
This study deals with overlaps used in TV program Ini Talk Show on Net TV. The objectives of this study were to find out the types of overlap and describe the effects of overlap in TV program. This research was conducted by using descriptive qualitative method. The data were dialogues in Ini Talk Show special episode on October, 16th 2016 which was taken from YouTube. The findings indicated that there were two types of overlap in ‘Ini Talk Show’ and they were competitive (39,39%) and non competitive (60,60%). The competitive overlap contributes the effects such as provoke laughter and create new ideas. Keywords : overlaps, competitive, non-competitive, talk show, net TV